2017
DOI: 10.5507/bp.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of B-type natriuretic peptide monitoring in outpatients with left ventricular assist device

Abstract: Serial measurement of BNP in outpatients with LVAD correlates with the occurrence of adverse events. Assessment of absolute values of BNP peak seems to have a similar accuracy to analysis of intra-individual variation of BNP and it is more practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the prognostic value of NP levels before LVAD implantation may be changed by the therapy itself. Nonetheless, several studies have shown that NP measurements and their fluctuations during LVAD therapy are strongly related to adverse outcome including mortality ( 28 , 29 , 45 ). These findings may suggest, that NP levels before implantation and during LVAD support may not have similar predictive value for all-cause mortality, as the hemodynamic support provided by the LVAD may change NP levels and the accompanied mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the prognostic value of NP levels before LVAD implantation may be changed by the therapy itself. Nonetheless, several studies have shown that NP measurements and their fluctuations during LVAD therapy are strongly related to adverse outcome including mortality ( 28 , 29 , 45 ). These findings may suggest, that NP levels before implantation and during LVAD support may not have similar predictive value for all-cause mortality, as the hemodynamic support provided by the LVAD may change NP levels and the accompanied mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, BNP levels before LVAD implantation were associated with MAEs between 2 weeks up to 2 years (42,43,45). In a sub-analysis, Hegarova et al demonstrated that although BNP was associated with adverse events up to 1.5 years after initial discharge, it was not associated with subsequent rehospitalizations (45). The two studies analyzing NT-proBNP levels found that it was not associated with complicated post-operative stay.…”
Section: Major Adverse Eventsmentioning
confidence: 97%
See 2 more Smart Citations
“…LVAD parameters such as flow rates may also be an indication of infectious complications [61]. Elevations of B-type natriuretic peptide (BNP) were also found to be a marker of serious adverse events in LVAD patients, including severe infections such as sepsis, mediastinitis and pump pocket infections [72]. Thrombosis, alteration in coagulation parameters, stroke, acute renal failure may also be early indicators of infection as well as more routine signs such as fever, leukocytosis and localizing signs and symptoms.…”
Section: Diagnosis Of Lvad Infectionsmentioning
confidence: 99%